Functional specialization of the left ventral parietal cortex in working memory - Langel, Jennifer; Hakun, Jonathan; Zhu, David C.; Ravizza, Susan M. (Frontiers in Human Neuroscience, 2014)
The function of the ventral parietal cortex (VPC) is subject to much debate. Many studies suggest a lateralization of function in the VPC, with the left hemisphere facilitating verbal working memory and the right subserving stimulus-driven attention. However, many attentional tasks elicit activity in the VPC bilaterally. To elucidate the potential divides across the VPC in function, we assessed the pattern of activity in the VPC bilaterally across two tasks that require different demands, an oddball attentional task with low working memory demands and a working memory task. An anterior region of the VPC was bilaterally active during novel targets in the oddball task and during retrieval in WM, while more posterior regions of the VPC displayed dissociable functions in the left and right hemisphere, with the left being active during the encoding and retrieval of WM, but not during the oddball task and the right showing the reverse pattern. These results suggest that bilateral regions of the anterior VPC subserve non-mnemonic processes, such as stimulus-driven attention during WM retrieval and oddball detection. The left posterior VPC may be important for speech-related processing important for both working memory and perception, while the right hemisphere is more lateralized for attention.